2002
DOI: 10.1152/physrev.00015.2002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Physiology of P2X Receptors

Abstract: P2X receptors are membrane ion channels that open in response to the binding of extracellular ATP. Seven genes in vertebrates encode P2X receptor subunits, which are 40–50% identical in amino acid sequence. Each subunit has two transmembrane domains, separated by an extracellular domain (∼280 amino acids). Channels form as multimers of several subunits. Homomeric P2X1, P2X2, P2X3, P2X4, P2X5, and P2X7 channels and heteromeric P2X2/3 and P2X1/5 channels have been most fully characterized following heterologous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

128
3,397
13
32

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,674 publications
(3,598 citation statements)
references
References 515 publications
128
3,397
13
32
Order By: Relevance
“…The use of the BzATP agonist gave us an EC 50 of 263±22 mM (Figure 2c). This is in line with the fact that P2X 7 R are more sensitive to BzATP than to ATP (North, 2002). ATP-evoked currents from MDA-MB-435s cancer cells were inhibited by human P2X 7 R antagonists KN62 and A740003 ( Figure 2d and supplementary Figure 1a).…”
Section: Human Cancer Cells Express Functional P2x 7 Rsupporting
confidence: 79%
See 1 more Smart Citation
“…The use of the BzATP agonist gave us an EC 50 of 263±22 mM (Figure 2c). This is in line with the fact that P2X 7 R are more sensitive to BzATP than to ATP (North, 2002). ATP-evoked currents from MDA-MB-435s cancer cells were inhibited by human P2X 7 R antagonists KN62 and A740003 ( Figure 2d and supplementary Figure 1a).…”
Section: Human Cancer Cells Express Functional P2x 7 Rsupporting
confidence: 79%
“…Extracellular ATP acts as a signalling molecule by activating plasma membrane G protein-coupled P2Y receptors and/or ligand-gated ion channels P2X receptors (Burnstock, 2006). Among the members of the P2X receptors family, the latest cloned P2X 7 receptors (P2X 7 R) (Rassendren et al, 1997) are very unique by different features, some of them are: (1) their sensitivity to ATP (North, 2002), (2) their facilitation under successive or sustained applications of agonist (Hibell et al, 2000;Roger et al, 2008Roger et al, , 2010a and (3) the appearance of a large, non-selective membrane pore after sustained stimulations with ATP (Pelegrin and Surprenant, 2006). Recently, several tumours have been shown to express P2X 7 R at unusually high levels (Adinolfi et al, 2002;Zhang et al, 2004;Slater et al, 2004a, b;Wang et al, 2004a;Raffaghello et al, 2006;Deli et al, 2007;Solini et al, 2008), however, their functionality and involvement in the physiology of cancer cells remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In migratory CPCs, we have recently confirmed the mRNA and protein level expression of certain P2X (P2X 1,4,5,6,7 , but not P2X 2 and P2X 3 ) and all P2Y receptors [86]. Our results suggest the functionality of P2Y 1 , P2Y 2 , P2Y 4 , as well as P2X 4 and P2X 6 receptor subtypes in CPCs, which shows a very good correlation with previous data implicating the P2 receptor subtypes P2X 6 , P2Y 4 and P2Y 14 to be key regulators in MSC commitment [91].…”
Section: P2 Purinergic Receptor Expression and Function During Chondrsupporting
confidence: 91%
“…Today seven members of the ionotropic (P2X [1][2][3][4][5][6][7] ) and eight members of the metabotropic (P2Y 1,2,4,6,[11][12][13][14] ) purinergic receptors have been cloned and identified in mammals [13,14]. In 6 case of P2X receptors the seven members of the subfamily refer to seven distinct subunits as discussed below.…”
Section: P2 Receptorsmentioning
confidence: 99%
“…As a group of membrane cation-selective receptor channels, P2X receptors interact with extracellular ATP [13]. It has been reported that ATP elicits discrete currents of P2X4R on microglia/macrophages [14]. In the latter, P2X4 receptors are involved in microglial activity in some pathological conditions.…”
Section: Introductionmentioning
confidence: 99%